A Comparison of Methods to Estimate Shovelnose Sturgeon Mortality in the Mississippi River Adjacent to Missouri and Illinois. (24th July 2013) - Phelps, Quinton E.; Vining, Ivan; Herzog, David P.; Dames, Ross; Travnichek, Vince H.; Tripp, Sara J.; Boone, Mark
Abstract: Mortality is a key parameter in understanding the dynamics of any fish population. We examined three methods to evaluate Shovelnose Sturgeon Scaphirhynchus platorynchus mortality (e.g., ratio of first year recruits to all recruits [Heincke's method], a linearized weighted catch curve, and an open system mark–recapture mortality approach). The Mississippi River was sampled in two distinct but connected geomorphic sections: upper Mississippi River (UMR; river kilometer 323–587) and the middle Mississippi River (MMR; river kilometer 0–322). All analyses were pooled across these areas due to potential emigration or immigration throughout both study reaches. Heincke's method estimated annual mortality at 16.9% for the full range of ages (9–23 years) with generally increasing estimates with decreasing age ranges considered (10–23, 11–23, 12–23, and so on). A linearized weighted catch curve that considered increasing estimates of mortality for the shorter age ranges generated an annual mortality estimate of 29.0%.d Four mark–recapture models were considered using the program MARK. The model with the greatest support was the model that provided estimates of annual mortality for each year and a single recapture probability. The annual mortality estimates from this model varied from 2.7% to 70.7% after correcting for tag loss. The best fit model with a single estimate of annual mortality was the one that estimated annual recapture probabilities for each year and had a mortality estimate of 34.6% (after correcting for tag loss, but not for immigration, emigration, or sampling effort). The three methods provided varying results, and our data indicated that a single method to estimate Shovlenose Sturgeon mortality rate may not be appropriate. As such, biologists must recognize that disparities in Shovelnose Sturgeon mortality rates may exist using various methods and should use caution when choosing which method will be employed to estimate sturgeon mortality. Received August 1, 2012; accepted May 16, 2013